99mTc-sestamibi and 18F-fluorodeoxyglucose imaging in patients with cardiogenic shock: A pilot study - Hua, Cuncun; Cai, Qizhe; Xi, Xiao-Ying; Lin, Mingming; Wang, Li; Li, Lina; Yao, Dandan; Liu, Xiaoyan; Zhao, Lei; Wang, Lefeng; Su, Pixiong; Xie, Boqia (Frontiers in Cardiovascular Medicine, 2022)
Background: Whether perfusion/metabolism imaging differs between matched ST-segment elevation myocardial infarction (STEMI) patients with and without cardiogenic shock (CS) remains unknown. Methods: Seventeen STEMI patients with CS (13 men, 60 ± 12 years) and 16 matched STEMI patients without CS (15 men, 54 ± 15 years) were prospectively recruited. All patients underwent baseline 99mTc-sestamibi/18F-fluorodeoxyglucose (FDG) imaging and echocardiography 6 ± 2 days post-infarction. Nine patients with CS and seven without had repeat imaging 98 ± 7 days post-infarction. The total perfusion deficit (TPD) and total FDG uptake deficit (TFD) were calculated to assess the percentages of impaired perfusion and metabolism over the left ventricle. Patients were followed up for 337 days (213–505 days) and the major adverse cardiac events (MACE) were recorded. Results: TPD was greater in patient with CS and was independently related to the presence of CS (OR: 4.36, p = 0.013). Both acute- and convalescent TFD were inversely related to the improvement ratio of LVEF (r values: -0.62, -0.73; both p < 0.05). MACE occurred in 16 patients (10 CS and 6 non-CS), and acute TFD was predictive of MACE in those with CS (HR: 2.06, p = 0.038). Conclusions: STEMI patients with CS had a significantly increased TPD, which was relevant to the presence of CS. Acute TFD was associated with improvement in LVEF, and was predictive of MACE in patients with CS.